“Far from the Shallow”? Aesthetics in Conservation Biology - Portera, Mariagrazia (Aisthesis, 2025)
What role, if any, does aesthetics play in the development of biological conservation strategies? Should we consider beauty – and, more broadly, the aesthetic dimension of human experience – as a source of bias that risks distorting scientific judgments (and, therefore, something to be carefully managed or even eliminated in the pursuit of objective scientific truth)? Or, conversely, might beauty be seen as a legitimate and powerful motivator – an emotional and perceptual force capable of promoting conservation efforts? The interplay between aesthetics, beauty, and scientific inquiry has long been a subject of relevant debate within the philosophy of science. In this paper, I aim to investigate the role that aesthetic values and perceptions play in the context of conservation biology – particularly in light of a growing and renewed interest among conservationists in the aesthetic aspects of nature and environmental engagement. The argument I will make is that eliminativist approaches – which frame the aesthetic mostly and primarily as a source of potential distortion – are based on an overly simplistic and impoverished conception of what “aesthetic” means.